DIPG-47. TSO500ctDNA sequencing reveals oncogenic mutations and copy number variations in the liquid biome of children with diffuse midline glioma. (3rd June 2022) - Bonner, Erin R; Harrington, Robin; Eze, Augustine; Bornhorst, Miriam; Kline, Cassie N; Dawood, Adam; Das, Biswajit; Chen, Li; Pauly, Rini; Williams, P Mickey; Karlovich, Chris; Peach, Amanda; et al.
Abstract: BACKGROUND : Molecular profiling of childhood CNS tumors is critical for diagnosis and clinical management, yet tissue access is restricted due to sensitive neuroanatomical locations. Moreover, CNS tumors including diffuse midline glioma (DMG) exhibit mutational heterogeneity and clonal evolution, which cannot be captured by upfront diagnostic biopsy alone. To address the lack of tumor visibility, and tprovide opportunity for longitudinal sampling, we validated and optimized a commercially available deep sequencing platform for analysis of circulating tumor DNA (TSO500ctDNA TM ). METHODS : In a proof-of-concept study, we defined the sensitivity, specificity, and clinical relevance of our novel ctDNA platform via analysis of paired tissue, CSF, and blood from children with DMG (n=10). Paired samples were assessed for concordance and sequencing results were compared to digital droplet PCR (ddPCR) detection of prognostic H3K27M mutation. RESULTS : DMG associated mutations in genes including H3-3A, H3C2, TP53, and ACVR1 were detected in ctDNA, including in CSF samples with low (<5ng) starting DNA input. Of 9 H3K27M mutations identified in tumor, 8 were present in CSF and 3 in plasma/serum, for a positive percent agreement with tumor results of 89% and 33%, respectively. Among CSF samples, H3.3K27M was detected in 6/6 cases, and H3.1K27M in 2/3 cases, with variant allele frequencies comparable to ddPCR results. CNVs including PDGFRA, KIT, and MDM4 gains were detected in CSF and paired tumor. Low frequency events including ACVR1, PIK3CA activating mutations and KRAS amplification were detected in CSF but absent from paired tumor, indicating tissue heterogeneity. Strategies to optimize ctDNA detection, including optimization of ctDNA isolation and adjustment of library QC metrics, were identified. CONCLUSION : Targeted ctDNA deep sequencing is feasible, can inform on clinically relevant tumor mutation and CNV profiling, and provides an opportunity for longitudinal monitoring of tumor genomic evolution in the liquid biome of children with CNS tumors.